EVALUATING THE SERVICE QUALITY OF COFFEE SHOP IN MANADO USING IMPORTANCE AND PERFORMANCE (IPA) ANALYSIS. (CASE STUDY: EXCELSO COFFEE) - Rumokoy, Farlane S. (Journal of Asean Studies on Maritime Issues, 2016)
Integrated of the service is determined by several sector. Addressing Asean Economic Community (ASC), increasing in service quality is the most high priority. coffee become a lifestyle there are many coffee shop that open in market, busy lifestyle also be the reason why some of society choose coffee shop to become the place that they can relax or gathering with friends. This also happen in Indonesia, where coffee shops are growing continiusly and rapidly, start from the traditional one until the modern one. The population in this research are the customer of Excelso coffee Manado Town Square. The sample of this research will be 100 customers of Excelso coffee Manado Town Square.